2023
DOI: 10.1302/0301-620x.105b9.bjj-2022-0713.r2
|View full text |Cite
|
Sign up to set email alerts
|

Birmingham Hip Resurfacing at 20 years

Rohit Dhawan,
David A. Young,
Anthony Van Eemeren
et al.

Abstract: AimsThe Birmingham Hip Resurfacing (BHR) arthroplasty has been used as a surgical treatment of coxarthrosis since 1997. We present 20-year results of 234 consecutive BHRs performed in our unit.MethodsBetween 1999 and 2001, there were 217 patients: 142 males (65.4%), mean age 52 years (18 to 68) who had 234 implants (17 bilateral). They had patient-reported outcome measures collected, imaging (radiograph and ultrasound), and serum metal ion assessment. Survivorship analysis was performed using Kaplan-Meier esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In a 2013 paper by Matharu et al, 24 the authors reported 100% survival in a highly selected group of male patients aged under 50 years with the diagnosis restricted to OA and excluding infections. More recently, Dhawan et al 25 studied a larger sample size of 234 BHR hips with OA. The cumulative implant survival rate at 20 years was 91.5% (95% CI 87.6 to 95.6), and female sex and smaller head size (< 48 mm) were found to be negative prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2013 paper by Matharu et al, 24 the authors reported 100% survival in a highly selected group of male patients aged under 50 years with the diagnosis restricted to OA and excluding infections. More recently, Dhawan et al 25 studied a larger sample size of 234 BHR hips with OA. The cumulative implant survival rate at 20 years was 91.5% (95% CI 87.6 to 95.6), and female sex and smaller head size (< 48 mm) were found to be negative prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative implant survival rate at 20 years was 91.5% (95% CI 87.6 to 95.6), and female sex and smaller head size (< 48 mm) were found to be negative prognostic factors. 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation